Capital Structure and the Profitability-Liquidity Trade-off - Omoregie, Osaretin Kayode; Olofin, Sodik Adejonwo; Ikpesu, Fredrick (International Journal of Economics and Financial Issues, 2019)
Theoretical guidance suggests a trade-off between profitability and liquidity in effect of capital structure decisions. This study investigates the link between capital structure and profitability-liquidity trade-off using descriptive and Panel-VAR analysis for 18 listed manufacturing companies in Nigeria. Findings from this study show no evidences of profitability-liquidity trade-off as function of capital structure. However, this study found that profitability and liquidity responds similarly to capital structure. Relative to equity share, debt ratios have negative effect on profitability and liquidity. Relative to asset, debt has positive effect on profitability and liquidity. Evidences further suggest that the way profitability and liquidity respond to capital structure is reliant on the business cycle position of the economy. Finance managers are advised to keep abreast the economic trend in the decision to adopt debt financing. Keywords: Capital Structure, Profitability-Liquidity Trade off, Panel-VAR JEL Classifications: G00, G32, M21 DOI: https://doi.org/10.32479/ijefi.7758